The Quaternary lions of Ukraine and a trend of decreasing size in Panthera spelaea - Marciszak, A.; Ivanoff, D.; Semenov, Y.; Talamo, S.; Ridush, B.; Stupak, A.; Yanish, Y.; Kovalchuk, O. (Journal of Mammalian Evolution, 2022)
The fossil record of the cave lion, Panthera spelaea, suggests a gradual decrease in body size, the process peaking just before the extinction of the species at the end of the Late Pleistocene. Such an evolutionary trend appears rather unusual for a large felid species and requires further investigation. This study reviews the cave lions of Ukraine, whose fossils are known from 46 localities dated from 800 kyr to 18–17 kyr ago, with a special emphasis on size changes through time. We describe several important finds including those of Panthera spelaea fossilis from Sambir, Panthera spelaea ssp. from Bilykh Stin Cave and Panthera spelaea spelaea from Kryshtaleva Cave. We make subspecific identifications of specimens from the region and focus on their size characteristics. Our analysis of Ukrainian cave lions agrees with the temporal trend of decreasing size, particularly accelerating during MIS 2, as exemplified by the extremely small female skull from Kryshtaleva Cave. We provide a direct AMS date for this specimen (22.0–21.5 cal kyr BP), which suggests that the Kryshtaleva lioness must have belonged to a Panthera spelaea spelaea population forced south by the spreading ice sheet. We discuss some palaeoecological aspects of the evolutionary history and eventual extinction of the cave lion. Finally, we review the subfossil records of the extant lion Panthera leo known from several Ukrainian sites archaeologically dated to 6.4–2.0 kyr BP. These finds most probably represent the Persian lion Panthera leo persica.
Keywords: Carnivora; Felidae; Skull; Body size; Pleistocene; Holocene